2006
DOI: 10.1074/jbc.m513380200
|View full text |Cite
|
Sign up to set email alerts
|

Distinct β-Arrestin- and G Protein-dependent Pathways for Parathyroid Hormone Receptor-stimulated ERK1/2 Activation

Abstract: The type I PTH/PTH-related peptide receptor (PTH1R), 2 a seventransmembrane receptor (7TMR) highly expressed in the kidney and bone, plays a fundamental role in the regulation of calcium homeostasis, as well as in bone formation and resorption. Ligands for PTH1R including PTHrp and PTH are involved in the etiology and treatment of disease processes such as hypercalcemia of malignancy and osteoporosis. The actions of PTH, however, are complex. PTH is known for both anabolic and catabolic effects on bone, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
351
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 435 publications
(368 citation statements)
references
References 46 publications
14
351
2
1
Order By: Relevance
“…Although ␤-arrestin 2 was identified as the predominant ␤-arrestin isoform interacting with 5-HT 2C receptors (Marion et al, 2004), depletion of either ␤-arrestin 1 or ␤-arrestin 2 by RNA interference strongly reduced 5-HT 2C receptor-mediated ERK1,2 phosphorylation. These results are coherent with several reports indicating that both ␤-arrestin isoforms are required for G protein-independent ERK1,2 signaling mediated by various GPCRs such as ␤ 2 -adrenergic and parathyroid hormone type 1 receptors (Gesty-Palmer et al, 2006;Shenoy et al, 2006). Nonetheless, activation of ERK1,2 by other GPCRs, including angiotensin II type 1a and V2 receptors, is critically dependent on ␤-arrestin 2, whereas ␤-arrestin 1 has a minor influence or an antagonistic action on ERK1,2 signaling (Ahn et al, 2004;Ren et al, 2005), indicating that specificity of ␤-arrestin isoforms for ERK signaling is dependent on the GPCR.…”
supporting
confidence: 81%
“…Although ␤-arrestin 2 was identified as the predominant ␤-arrestin isoform interacting with 5-HT 2C receptors (Marion et al, 2004), depletion of either ␤-arrestin 1 or ␤-arrestin 2 by RNA interference strongly reduced 5-HT 2C receptor-mediated ERK1,2 phosphorylation. These results are coherent with several reports indicating that both ␤-arrestin isoforms are required for G protein-independent ERK1,2 signaling mediated by various GPCRs such as ␤ 2 -adrenergic and parathyroid hormone type 1 receptors (Gesty-Palmer et al, 2006;Shenoy et al, 2006). Nonetheless, activation of ERK1,2 by other GPCRs, including angiotensin II type 1a and V2 receptors, is critically dependent on ␤-arrestin 2, whereas ␤-arrestin 1 has a minor influence or an antagonistic action on ERK1,2 signaling (Ahn et al, 2004;Ren et al, 2005), indicating that specificity of ␤-arrestin isoforms for ERK signaling is dependent on the GPCR.…”
supporting
confidence: 81%
“…We have previously reported that stimulation of PTH1R with PTH-(1-34) leads to both G protein-dependent and ␤-arrestin-dependent signaling, whereas stimulation with the PTH analogue [D-Trp 12 ,Tyr 34 ]PTH-(7-34), which is an inverse agonist (PTH-IA), results in only ␤-arrestin signaling (19). As shown in Fig.…”
Section: Distinct Conformational Changes In ␤-Arrestin Upon Activatiomentioning
confidence: 88%
“…PTHR1 also stimulates Gα q -mediated activation of protein kinase C (PKC). In addition, PTH activates β-arrestin-mediated activation of extracellular regulated kinase (ERK) signaling [39,40]. β-arrestin is also involved in desensitization of cAMP signaling by PTHR1.…”
Section: General Aspectsmentioning
confidence: 99%